Individual training-load and aerobic-fitness variables in Premiership soccer players during the precompetitive season - Manzi, V.; Bovenzi, A.; Impellizzeri, F. M.; Carminati, I.; Castagna, C. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to examine the association between individual measures of internal training load (training impulse [TRIMPi]) and aerobic-fitness and performance variables in premiership male soccer players. Eighteen Premiership soccer players (age 28.4 ± 3.2 years, height 182 ± 5.3 cm, body mass 79.9 ± 5.5 kg) performed treadmill tests for VO2max and ventilatory threshold (VT) and speed at blood-lactate concentration of 4 mmol/L (S4) on separate days pre and post 8 weeks of training (preseason). The Yo-Yo Intermittent recovery test (Yo-Yo IR1) performance was assessed pre and post preseason training as well. The TRIMPi was calculated using individual lactate and heart-rate profiles and assessed in each training session (n = 900). The results showed that TRIMPi was large to very-large associated with percentage changes in VO2max (r = 0.77, p = 0.002), VT (r = 0.78, p = 0.002), S4 (r = 0.64, p = 0.004), and Yo-Yo IR1 performance (r = 0.69, p = 0.009). Regression analyses showed that a weekly TRIMPi >500 AU was necessary to warrant improvements in aerobic fitness and performance in premiership male soccer players during the precompetitive season. It is concluded that TRIMPi is a valid and viable tool to guide training prescription in male premiership soccer players during the preseason.